Supplemental Material: A reevaluation of the tectonic history of the Dashwoods terrane using in situ and isotope-dilution U-Pb geochronology, western Newfoundland - E.B. Hodgin (9339606); (281964) (2022)
Detailed methods, Figures S1 and S2, and Tables S1 and S2